Studies on the "ERA" strain of rabies virus in Brazil. I. Distribution of the virus in the organism of inoculated cattle and formation of inclusions in the central nervous system - Silva, Renato Augusto da; Silva, Norma Moraes da; Menezes, Patino Roberto Valadão (Pesquisa Agropecuaria Brasileira, 2014)
Rabies virus, "ERA" strain, inoculated by intra-muscular route into the masseter muscle was capable of localizing in the salivary glands, brain, cerebellum, bulbus and spinal cord. The "ERA" strain determined the appearence of inclusions, in the cytoplasm of the neurons of bulbus and spinal cord, which resembled Negri bodies. Fine granular acidophile material diffusely dispersed in the cytoplasm was encountered. The viral rabies antigen was detected in high concentration in the bulbus, spinal cord and salivary glands, by fluorescent antibodies techniques. The rabies virus was not recovered from the nervous tissues, salivary glands saliva of mice.